Grouping of decathlon disciplines - Woolf, A.; Ansley, L.; Bidgood, P. (Journal of Quantitative Analysis in Sports, 2007)
The 10 disciplines in the decathlon can be broadly characterised as running, jumping and throwing. However, these simplistic characteristics may not represent the groupings defined by performances in the decathlon. The identification of groups may reveal a recondite advantage for athletes who excel in particular disciplines. Therefore this study used cluster analysis to determine the groupings inherent within the decathlon disciplines. The data set was derived from the top 173 decathletes between the years 1986 to 2005. Six clustering methods were applied to a Euclidean proximity matrix. The highest number of clusters common to all the methods was accepted as the solution. All six methods produced the same 3-cluster ([100m 400m 110H LJ PV HJ][SP DT JT][1500m]), 4-cluster ([100m 400m 110H LJ PV][SP DT JT][HJ][1500m]) and 5-cluster ([100m 400m 110mH LJ][SP DT JT][PV][HJ][1500m]) solutions. Stability tests confirmed the consistency of all the solutions. The 10 disciplines of the decathlon form into five groupings, which can be adequately explained from a physiological perspective. The clustering suggests that athletes who perform better at the sprint/track disciplines may obtain an advantage in the decathlon.